2019
DOI: 10.1002/pmh.1455
|View full text |Cite
|
Sign up to set email alerts
|

Personality profiles as potential targets for intervention: Identification and replication

Abstract: The alternative dimensional model of personality disorder (PD) diagnosis, based on personality‐functioning impairment and pathological traits, opens the door for tailoring treatments to individuals with more homogeneous personality profiles than diagnostic categories. Such a transdiagnostic PD treatment approach requires robust, replicable, personality‐relevant dimensions, which we found using a large battery of self‐report measures: Self‐pathology and negative affectivity (NA) traits, interpersonal pathology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
(35 reference statements)
3
13
1
Order By: Relevance
“…BPD is one of the very few diagnoses that would appear to belong to both an "internalized" (distress) and an "externalized" (antagonistic) spectra according to the recently developed Hierarchical Taxonomy of Pathology (HiTOP; [67, p. 462]), a dimensional nosology of mental disorders based on their observed covariation across empirical studies; the present result tend to support the validity of this distinction for BPD. Our results also bear some resemblance with those reported by Clark et al [68] in the only study thus far, to our best knowledge, that used the AMPD framework to identify subgroups of outpatients (although not speci cally borderline); they found evidence for three pro les, (a) a group with primarily interpersonal problems; (b) one with selfpathology and emotional dysregulation/negative affectivity; and (c) a more severe group with both types of problems. While there are evident resemblances between our Moderate borderline pathology with Identity problems and Depressivity pro le and Clark et al's self-pathology/negative affectivity pro le, and between the severe pro les found in both studies, there are also divergences between the two classi cations, as impulsivity (in our study) and interpersonal pathology (in Clark et al's) appeared to have inconsistent value across studies to assign patients to pro les.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…BPD is one of the very few diagnoses that would appear to belong to both an "internalized" (distress) and an "externalized" (antagonistic) spectra according to the recently developed Hierarchical Taxonomy of Pathology (HiTOP; [67, p. 462]), a dimensional nosology of mental disorders based on their observed covariation across empirical studies; the present result tend to support the validity of this distinction for BPD. Our results also bear some resemblance with those reported by Clark et al [68] in the only study thus far, to our best knowledge, that used the AMPD framework to identify subgroups of outpatients (although not speci cally borderline); they found evidence for three pro les, (a) a group with primarily interpersonal problems; (b) one with selfpathology and emotional dysregulation/negative affectivity; and (c) a more severe group with both types of problems. While there are evident resemblances between our Moderate borderline pathology with Identity problems and Depressivity pro le and Clark et al's self-pathology/negative affectivity pro le, and between the severe pro les found in both studies, there are also divergences between the two classi cations, as impulsivity (in our study) and interpersonal pathology (in Clark et al's) appeared to have inconsistent value across studies to assign patients to pro les.…”
Section: Discussionsupporting
confidence: 88%
“…Ultimately, the de ning test of the validity of the pro les identi ed in the present analysis will rely on their clinical usefulness, i.e., whether they are clinically helpful for treatment planning and contracting; whether they provide relevant information on treatment trajectories, including response to treatment and dropout risk; and whether some treatment approaches might be better suited for one patient pro le or another [16]. Clark et al [68] have suggested that AMPD-based pro les can be useful for differential treatment planning based on transdiagnostic treatment targets (e.g., emotional dysregulation, interpersonal issues), a suggestion with which we concur. An intriguing avenue for future research based on our pro les would be to determine whether the Low borderline pathology with Impulsivity or the Moderate borderline pathology with Identity problems and Depressivity has a better treatment prognosis, and whether tailoring the treatment to these categories (e.g., focusing on impulsivity/disinhibition with the former and on identity/depressivity issues with the latter) might prove effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such work should also inform and be informed by clinical practice as efforts to develop more effective interventions for personality pathology continue. Future therapy approaches that target core self and other impairments and maladaptive traits, as well as tailor interventions with reference to severity of personality pathology and the patient’s trait profile would serve to advance the next generation of treatment models [54-56]. These and related future advancements are facilitated by defining personality pathology in terms of personality processes reflecting impairments in self and other functioning and distinguishing the severity of personality impairment from individual differences in its expression [1].…”
Section: Discussionmentioning
confidence: 99%
“…Along these same lines, Clark and colleagues discuss the potential value of using evidence‐based personality profiles as targets for psychological interventions. Using a structural model derived from both personality disorder traits and dimensions of impaired functioning, Clark et al identified three groups of individuals with different profiles of scores and suggested different treatment approaches thought to optimally address each group's pattern of personality and functioning deficits.…”
mentioning
confidence: 99%